High-rate biological hydrogen and methane production from pome in a two-stage anaerobic hybrid reactor / Bidattul Syirat Zainal - Bidattul Syirat , Zainal (2019)

(untitled)
This study was divided into three phases, viz. i) batch study, ii) start-up study using upflow anaerobic sludge fixed film (UASFF) bioreactor, and iii) optimization study. UASFF bioreactor is a type of bioreactor configuration similar to the type used by industries for the treatment of wastewaters. It is a hybrid system that combines two compartments for providing granular and fixed biomasses in a single bioreactor. In this study, a 2.5 L and 3.5 L of H2-UASFF and CH4-UASFF bioreactor units, respectively, were successfully operated for palm oil mill effluent (POME) treatment. An initial experiment was done to evaluate the nature of POME wastewater by conducting a batch study using a 160-mL serum bottle, under anaerobic condition. A batch study for biohydrogen production was conducted using raw POME and POME sludge as a feed and inoculum respectively. Response Surface Methodology (RSM) was used to design the experiments. Experiments were conducted at different reaction temperatures (30-50°C), inoculum size to substrate ratios (I:S) and reaction times (HRT) (8-24 h). Although the highest COD removal efficiency was 49.09% at 24 h, 50°C and 10:90 (I:S), however, based on the optimization study using RSM, the optimum condition of biohydrogen production was achieved with COD removal efficiency of 21.95% with hydrogen yield of 28.47 mL H2 g-1 COD removed (2.22 mg H2 g-1 COD removed). The I:S ratio was 40:60, with a reaction temperature of 50°C at 8 h of reaction time. The next experiment was done in a two-stage UASFF bioreactor in order to study its performance. A start-up study was conducted to produce biohydrogen and biomethane from POME. During this period of continuous operation, the HRT and temperature were adjusted in order to optimize the condition for biogas production. After 59 days of operation, using 100% raw POME led to a total COD removal of 83.70%, average gas production rates of 5.29 L H2 d-1 (57.11% H2) and 9.60 L CH4 d-1 (94.08% CH4), in H2-UASFF unit and CH4-UASFF unit, respectively. This work concludes that the two-stage UASFF bioreactor operating at a final HRT of 4 h and temperature of 43°C in H2-UASFF unit and 24 h HRT, 43°C in CH4-UASFF unit has taken a period of two months for start-up. The third phase was done in order to find the optimum conditions for two-stage UASFF bioreactor in treating POME. Two variables, i.e. temperature (37-70°C) and HRT (3-9 h) was examined in H2-UASFF unit and the same temperature and dark fermentation effluent was used as a substrate (12 – 20 g CODL-1) in CH4-UASFF unit. At optimum temperature and HRT of 57°C and 7 h, respectively, maximum hydrogen production rate of 10.39 L H2 d-1, hydrogen yield of 0.95 L H2 g-1 CODremoved and 35.88% of COD removal were observed. In CH4-UASFF unit, at 24 h HRT, 76% of total COD removal efficiency was achieved with methane production rate of 15.63 L CH4 d-1, methane yield of 0.803 L CH4 g-1 CODremoved, COD removal efficiency of 66.28%, and 93.31% of CH4 content at optimum temperature and substrate concentration of 54°C and 12 g COD L-1, respectively. These findings proved that the integrated system can enhance biogas production rate, yield and efficiently treating POME wastewater under a short period of time with low substrate concentration and thermophilic condition.